Developmental decrease in size of peripheral receptive fields of single chorda tympani nerve fibers and relation to increasing NaCl taste sensitivity - Nagai, T (J Neurosci, 1988)
During development in rats, sheep, and humans, the taste system acquires increasing responsiveness to NaCl, compared with a variety of other salts and chemicals. To better understand the neural basis of changes in salt taste responses, we studied receptive field size and response properties of single chorda tympani nerve fibers in fetal, perinatal, and postnatal sheep. Individual fungiform papillae were stimulated electrically with 5 microA anodal current to determine the location and number of papillae in receptive fields. Response characteristics of NH4Cl, NaCl, and KCl were determined for the entire field. Receptive fields were dissected for later histological reconstruction and taste bud identification. Median receptive field size decreased during development. Field sizes in lambs were smaller than those in younger animals. This decrease was accompanied by an increase in the NaCl/NH4Cl response ratio of single fibers and an increase in the proportion of fibers and associated fields that responded with higher frequency to NaCl, compared with NH4Cl. In addition, for fibers across all age groups, receptive field size correlated negatively with the NaCl/NH4Cl response ratio; that is, fields most responsive to NaCl had fewer papillae than those most responsive to NH4Cl. For all fibers, receptive field size correlated with response frequencies to NH4Cl and KCl but not NaCl. For NaCl-best fibers, receptive field size correlated with the response frequencies to all 3 salts. There was no relation between number of taste buds in a single fungiform papilla and the response frequency elicited during electrical stimulation of the papilla.